How to escape from sudden death: a challenging case of a rare cardiomyopathy with an unexpected twist - Luísa Pinheiro; Margarida de Castro; Filipa Cordeiro; Tamara Pereira; Francisco Ferreira; Víctor Sanfins; António Lourenço; Olga Azevedo (Monaldi Archives for Chest Disease)
A 59-year-old man presented with recurrent syncope and was found to have bifascicular block and severe concentric left ventricular hypertrophy. A permanent double-chamber pacemaker was implanted. Initial investigations revealed elevated transferrin saturation and homozygosity for the HFE gene p.C282Y variant, indicating hereditary hemochromatosis. However, cardiac magnetic resonance imaging showed inferolateral intramyocardial late gadolinium enhancement (LGE) without evidence of iron deposition, raising suspicion for Fabry disease (FD). This was confirmed by low α-galactosidase A activity and detection of the pathogenic GLA p.F113L variant. Multisystemic evaluation revealed additional FD manifestations, and enzyme replacement therapy was initiated, later switched to oral migalastat. The patient subsequently developed left ventricular systolic dysfunction and apical thrombus, attributed to high ventricular pacing burden, and was scheduled for cardiac resynchronization therapy (CRT) device implantation. Before the upgrade, he suffered a cardiac arrest due to ventricular fibrillation, associated with coronary artery stenosis, requiring CRT-D implantation. Despite device therapy and amiodarone initiation, recurrent ventricular tachycardias (VTs) persisted, leading to percutaneous coronary intervention and electrical stability. This case highlights the diagnostic complexity of overlapping cardiac diseases, the significance of inferolateral LGE and conduction abnormalities in suspecting FD, and the crucial role of family screening. The p.F113L variant is associated with late-onset, cardiac-predominant FD, where bradyarrhythmias are more prognostically relevant, but concurrent pathologies like coronary artery disease must be considered in VT presentations.